A systematic review and novel classification of listing tools to improve medication in older people - Pazan, Farhad; Kather, Jonathan; Wehling, Martin (European journal of clinical pharmacology, 2019)
PurposeSuboptimal drugs therapy is a threat to older people, and listing tools providing guidance are developed to address this problem.MethodsA systematic review was performed to identify and analyze such tools published until February 2018. A novel categorization was developed to separate patient-in-focus listing approaches (PILA) providing disease-related positive and negative guidance from drug-oriented, mostly negative listing approaches (DOLA, DOLA+: with disease specification).ResultsIn total, 76 tools were identified; only 9 were classified as PILA, 26 as DOLA, and 38 as DOLA+. Three DOLA(+) only address dementia. Most tools were developed in Europe or the USA and address community-dwellers. Thirty-two utilized a Delphi process, and only 10 provide a scoring system. Twenty tools utilize a questionnaire but no structured guidance or answers. Importantly, only 12 interventional clinical trials were identified reporting not only medication quality measures, but also clinical endpoints (e.g. falls, adverse drug reactions, hospitalization). For PILA, 4 trials showed positive, one negative clinical effects of a controlled intervention, for DOLA(+) 1 was positive, 7 negative (Fisher’s exact test p < 0.05).DiscussionAn abundance of listing tools has been created. DOLAs that may be applied without intricate patient knowledge prevail over PILAs by sevenfold; unfortunately their clinical validation seems to be far less successful than that of patient-initiated approaches.ConclusionDrug therapy in older people has to be tailored to their individual, very divergent needs; tools requiring detailed medical knowledge about the patient as the starting point for medication optimization provide the best support.
Gesehen am 21.05.2019